The use of board games and their development principles: a case review - Rito, P. N. (2020)
Board games, or card games, are a reality that has been part of the past and the present, of several generations of people. These objects are a good tool to provide people of all ages, practical skills and assist them in developing their knowledge on all subjects. These games create a competitive, non-threatening and fun environment, encouraging skills development. There have also been some reports in the literature about the benefits of these games when explored in the classroom, on certain topics, and which are related to themes that are part of the programs of some disciplines, such as mathematics, programming or history. But it is not only about these topics that evidence emerges, since the use of these objects can help in the relationship between students, as there are reports that their use promotes dialogue, causes discussions and problem solving in teams. Other highlights in the literature are that an effective game allows organizing information into conceptual structures that provide and transmit, through analogies and / or metaphors, new information. This premise is interesting, because there is a possibility to respond to people who learn through concrete information and to others through metaphors. Thus, there is support for different learning styles. But not everything goes as smoothly as, for some educators, the use of games in the classroom and in certain activities reduces the time available, for example, to practice solving math problems, when in fact, and for these educators, these games should be used in other contexts. This article is part of a research work on the effective use of modern board games in the classroom. The objective is to perceive and contextualize this effective use and what possible connections there are with the mechanics that are normally dynamized by educators, reflecting on the dynamics developed in the design of these games. Another interesting point about the theme of this work is the construction of a reference about these use cases, more specifically those that were explored in the context of mandatory education in Portugal.